Asian transnational security challenges : emerging trends, regional visions - Ziemke-Dickens, Caroline; Droogan, Julian; Council for Asian Transnational Threat Research (PICT) (Sydney : Council for Asian Transnational Threat Research (PICT), Centre for Policing, Intelligence and Counter Terrorism (PICT), Macquarie University, 2010)
'This publication is the product of the CATR Emerging Threats Survey, a year-long collaborative research project conceived by the CATR Board of Governors, carried out by CATR member institutions, and coordinated by the Institute for Defense Analyses with support from the Advanced Systems and Concepts Office of the United States Defense Threat Reducation Agency and the Centre for Policing, Intelligence and Counter Terrorism (PICT) at Macquarie University, Sydney, Australia.'
Includes bibliographical references (p. 199-218)
Keywords: National security -- Asia -- 21st century; Terrorism -- Asia -- Prevention